Report on the D32 CCR5 variant in the Sudanese Shagia tribe - Kempińska-Podhorodecka, Agnieszka; Knap, Oktawian; Parczewski, Miłosz; Bińczak-Kuleta, Agnieszka; Parafiniuk, Mirosław (Anthropological Review, 2008)
The focus on small isolated populations provides important insights into the factors affecting the distribution of inheritable traits. Here, we present a report on the distribution of the CCR5 Δ32 mutation in the so far unstudied innate Sudanese population of Shagia people. The genetic material (buccal swabs) was collected from 125 individuals living in three African villages, Abu Haraz, Shibabit and El Higiena. The DNA was extracted, the polymorphic site PCR-amplified with a pair of specific primers flanking the Δ32 CCR5 mutation and reaction products electrophoretically separated in agarose gel. In the Abu Haraz and Shibabit villages, all investigated individuals were found to be homozygous for the wildtype of the receptor, while in El Higiena village one wt/D32 homozygote was identified with the remaining individuals homozygous for non-mutated CCR5. The frequency for the Δ32 CCR5 allele was 0,4%, with Δ32/wt genotype frequency of 0,8%. This is the first report on the presence of the Δ32 CCR5 allele not only in the genetically isolated Shagia tribe but also in the region of the Sudan.